Microwave assisted palladium catalyzed carbon-carbon bond formation to synthesise novel benzimidazole derivatives and their Photophysical properties, molecular docking, and DFT study - Vijayabharathi Sundharaj; S. Sarveswari (Heliyon)
In the present study, novel benzimidazole compounds are synthesized, utilizing Suzuki coupling and acid-amine coupling reaction. The formation of all synthesized derivatives was confirmed through various spectroscopic techniques, including 1H, 13C, Carbon DEPT-135, H-H COSY, HSQC, and HRMS. The UV–Vis and fluorescence spectra of all synthesized compounds were recorded. Particularly, among all synthesized compounds, compound 9o (304.06 nm) exhibited the higher λmax in UV–Vis spectroscopy, while compound 9j (396.16 nm) exhibited the highest emmision intensity in fluorescence spectroscopy. Furthermore, density functional theory (DFT) calculations were performed at the B3LYP/6-31G′(d,p) foundational level set. These calculations aimed to predict the chemical reactivity of the newly synthesized benzimidazole derivatives by assessing parameters such as the HOMO-LUMO energy gap value, ionization potential, electrostaic potential, electron affinity, electronegativity, global hardness, and softness energy values. Subsequently, a molecular docking analysis was performed on all synthesized derivatives on a protein associated with Bcl-2 in conjunction with venetoclax, with compound 9g (−10.77 kcal/mol) indicating the most significant binding affinity among the compounds investigated.